EVALUATING COHESION AND COHERENCE IN THESIS INTRODUCTIONS: A THEMATIC PROGRESSION ANALYSIS OF EFL STUDENTS’ TEXTS - Ade Ismail; Indry Widyasti Anwar; Sartika Putri Sailuddin; Hijril Ismail (Universitas Kuningan, 2024)
This study was conducted to determine EFL students' skills in writing a thesis introduction. Five student dipilih berdasarkan level keterampilan menulis di mana kelima mahasiswa ini merupakan mahasiswa terbaik. The analysis method used is thematic progression. The student texts were analyzed for each paragraph, then counted how many sentences applied the Constant Theme Pattern, Linear Theme Pattern, Split Theme Pattern, and Derived Theme Pattern. The findings indicated that from the total 194 sentences being analysed, seventy-six employed this pattern to connect ideas. Another aspect of connecting ideas is the cohesive devices used. The higher application of definite articles, pronouns and word repetition is evident. Students majorly drew definite articles and demonstrative pronouns (e.g. this, that) which then makes it adaptable for readers to follow their idea development in a paragraph. Regarding the coherence, students in this study significantly relied on the theme of sentences to be the source of their idea development. Despite the clarity and coherence being well managed in students’ writing, the link between ideas can still be diversed by employing other patterns. Moreover, some rhemes contain new information that need further elaboration as the text grows. Students have applied the rules of thematic progression, although there are several sentences that do not comply with the principles of cohesion and coherence. Guidance and feedback from the lecturer is really needed so that writing skills are maintained, especially in writing the introduction to the thesis.